CONDITIONS FOR OCCURRENCE OF VIBRATIONS IN WOOD MILLING MACHINES (Innovation in Woodworking Industry and Engineering design, 2026)
The work of each machine is inevitably accompanied by the occurrence of vibrations which have adverse effects in many directions. Vibrations are among the main factors influ-encing woodworking machines’ effectiveness, cutting tools durability and the quality of the processed surface.In this review the main terms characterizing the oscillations are presented. The principal conditions for vibrations generation based on cutting system of the machine, cutting tools, cutting regime and the processed material, are also covered.